(untitled) (Journal of the College of Basic Education, 2023)
Lead oxide films with a thickness of (210, 250, 300) nm were prepared by thermal chemical decomposition method on borosilicate glass bases at a temperature of (400 oC).The optical properties were studied based on the absorbance and transmittance spectra of the prepared films in the wavelength range (390-900) nm. It was found that the absorbance increased while the transmittance decreased when the thickness of the membrane increased.The following optical constants were calculated: reflectance, refractive index, and the forbidden energy gap for direct transmission, which decreases with increasing thickness. While the absorption coefficient and the inertia coefficient increase with the increase of the thickness of the film.